Faktor-faktor yang Berperan dalam Keputusan Konsumen Mengkonsumsi Produk Susu Bubuk Dancow Instant Enriched di Kota Denpasar - LUH GEDE GITA SARASWATI; I KETUT SUAMBA; NYOMAN PARINING (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
Abstract Factors that Plays Role in Consumer’s Decision of Consuming Dancow Instant Enriched Powdered Milk in Denpasar. The purpose of this study was to determine any factors that play a role in the consumer's decision to consuming Dancow Instant Enriched milk powder , the role of indicators to variable, and the role of indicators of consumer’s decision to consume Dancow Instant Enriched milk powder in Denpasar. Data collection method used in this research is interview and documentation study. Method used is quantitative method, where variables are measured with an ordinal scale. The data is then processed using confirmatory factor analysis. Based on the results of this study concluded that the variables that have the largest share of the consumer's decision is variable X4, X2 and X5. X6 has the lowest variable part of the consumer's decision to consume Dancow Instant Enriched milk powder. Indicators of variables X1, X2, X3, X5, and X6 are equally important by 50%. indicator x43 has the biggest role value to variable X4 which is equal to 28.8%. Indicator x81 has the biggest role value to variable X8 which is equal to 42.2%. Indicators that have the biggest role to the consumer's decision to consume Dancow Instant Enriched milk powder  is  indicator x43 with the role value 9.81%. Indicators that have the second biggest role value  is indicator x42 with 9.54%. The role value of  indicators x21 and x22 is equal to 9.18%. Keywords: consumer decision, factor analysis, Dancow Instant Enriched